Differential expression of melanopsin isoforms Opn4L and Opn4S during postnatal development of the mouse retina. - Steven Hughes; Laura Welsh; Christiana Katti; Irene González-Menéndez; Michael Turton; Stephanie Halford; Sumathi Sekaran; Stuart N Peirson; Mark W Hankins; Russell G Foster (PLoS ONE, 2012)
Photosensitive retinal ganglion cells (pRGCs) respond to light from birth and represent the earliest known light detection system to develop in the mouse retina. A number of morphologically and functionally distinct subtypes of pRGCs have been described in the adult retina, and have been linked to different physiological roles. We have previously identified two distinct isoforms of mouse melanopsin, Opn4L and Opn4S, which are generated by alternate splicing of the Opn4 locus. These isoforms are differentially expressed in pRGC subtypes of the adult mouse retina, with both Opn4L and Opn4S detected in M1 type pRGCs, and only Opn4L detected in M2 type pRGCs. Here we investigate the developmental expression of Opn4L and Opn4S and show a differential profile of expression during postnatal development. Opn4S mRNA is detected at relatively constant levels throughout postnatal development, with levels of Opn4S protein showing a marked increase between P0 and P3, and then increasing progressively over time until adult levels are reached by P10. By contrast, levels of Opn4L mRNA and protein are low at birth and show a marked increase at P14 and P30 compared to earlier time points. We suggest that these differing profiles of expression are associated with the functional maturation of M1 and M2 subtypes of pRGCs. Based upon our data, Opn4S expressing M1 type pRGCs mature first and are the dominant pRGC subtype in the neonate retina, whereas increased expression of Opn4L and the maturation of M2 type pRGCs occurs later, between P10 and P14, at a similar time to the maturation of rod and cone photoreceptors. We suggest that the distinct functions associated with these cell types will develop at different times during postnatal development.